THE INTANGIBLE CULTURAL HERITAGE IN SULUK WUJIL: SEMIOTICS ANALYSIS - Setiawan Nugraha, Deden Novan (Journal Sampurasun : Interdisciplinary Studies for Cultural Heritage, 2019)
Cultural heritage is a legacy of the past reflect the identity of a group ethnic or nation. Cultural heritage contains not only traditional values but also belief systems. One of intangible cultural heritage is Suluk Wujil. Suluk Wujil begins with the journey of a young man named Wujil who tries to find information about the chosen religion to the deepest secret. During the ten years of his journey, Wujil has not found the true truth about the nature of divinity and the meaning of his existence in the universe even though he has studied various kinds of science and knowledge. This research is in the form of qualitative descriptive with Roland Barthes’s semiotics as the main instrument for analyzing data. The identified sign system is interpreted in two stages of significance (language level and myth level). Oriented to the core myths of Sufism, the illustrated rules of Makrifatullah are divided into four categories; the introduction stage (a human being must escape in understanding one’s own authenticity in order to reach the highest epistemology in the universe, search plan (the depth of the heart of a human being is a sacred place where divine nature is buried as the greatest secret (sirru sirr), the practice of reaching Makrifatullah must be totality and continuity through words (qouli), deeds (fi’li), mind (aqli), and heart (qolbu), and reflection of application (awareness of tolerance among fellow creatures (habluminannas) as the result of perfect understanding of the reality of divinity (habluminallah).